2008
DOI: 10.1111/j.1365-2265.2008.03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the PTPN11 gene in idiopathic short stature children and Noonan syndrome patients

Abstract: Considering that no mutations were found in the present cohort with NS-related signs, it is unlikely that mutations would be found in unselected ISS children. The van der Burgt et al. criteria are adequate in attaining NS diagnosis and selecting patients for molecular studies. Mutations in the PTPN11 gene are commonly involved in the pathogenesis of NS but are not a common cause of ISS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
4
0
8
Order By: Relevance
“…Typical face and any other major sign or two minor signs establishes the diagnosis of NS, whereas patients with suggestive NS face need two major or three minor criteria to confirm the NS diagnosis. Analyses of clinical features in NS patients, who had their diagnosis confirmed by molecular study, demonstrated that no isolated clinical characteristic can ensure the diagnosis of NS; however, the van der Burgt et al criteria, which take in account the facial features, growth pattern, chest deformity and cardiac defects, have been shown to be an accurate tool for NS diagnosis [22]. For these reasons, we recommend the use of this scoring system by endocrinologists during the evaluation of short stature children to facilitate the recognition of patients with NS.…”
Section: Clinical Diagnosis Of Noonan Syndromementioning
confidence: 99%
“…Typical face and any other major sign or two minor signs establishes the diagnosis of NS, whereas patients with suggestive NS face need two major or three minor criteria to confirm the NS diagnosis. Analyses of clinical features in NS patients, who had their diagnosis confirmed by molecular study, demonstrated that no isolated clinical characteristic can ensure the diagnosis of NS; however, the van der Burgt et al criteria, which take in account the facial features, growth pattern, chest deformity and cardiac defects, have been shown to be an accurate tool for NS diagnosis [22]. For these reasons, we recommend the use of this scoring system by endocrinologists during the evaluation of short stature children to facilitate the recognition of patients with NS.…”
Section: Clinical Diagnosis Of Noonan Syndromementioning
confidence: 99%
“…Olgumuzun, NS'nin klinik bulgularından biri olan non-obstrüktif hipertrofik kardiyomyopatiye ikincil gelişen paroksismal atrial fibrilasyonun neden olduğu embolik iskemik inme geçirdiği düşünüldü. NS tanı kriterlerinin kullanımlarındaki kısıtlılıklar nedeni ile 1994 yılında van der Burgt ve arkadaşları tarafından önerilen ve klinik bulgulara dayanan yeni kriterlerin güvenilir olduğu başka bir çalışmada da bildirilmiştir (7,8). Yeni kriterlere göre bu olgu tipik yüz görünümüne eşlik eden iki minör bulgu (hipertrofik kardiyomyopati, yele boyun) nedeni ile kesin NS tanısı aldı.…”
Section: Discussionunclassified
“…crescimento A baixa estatura de início pós-natal é uma das características clínicas mais freqüentemente observadas na SN, afetando cerca de 70% a 83% dos pacientes (8,9). Durante a infância observa-se crescimento paralelo à curva de referência (10) (Figura 2) com escore de desviospadrão de altura em média de -3 (11)(12)(13)(14), observando-se atraso de um a dois anos na idade óssea.…”
Section: Malaquias Et Alunclassified
“…Estudos realizados avaliando o eixo GH/ IGF-1 em pacientes com SN apresentaram resultados contraditórios. A resposta aos testes de estímulo de secreção de GH é usualmente normal (9). A avaliação da secreção espontânea de GH em crianças com SN, por meio do ritmo de GH, mostra secreção diminuída em um estudo (16) e normal com tendência a ser elevada em dois outros (17,18).…”
Section: Malaquias Et Alunclassified
See 1 more Smart Citation